Analysis of Simulation Methods for Far-end Crosstalk Cancellation - Lafata, Pavel; Jares, Petr (Společnost pro radioelektronické inženýrství, 2011)
The information capacity of current digital subscriber lines is limited mainly by a crosstalk in metallic cables. The influence of near-end crosstalk (NEXT) can be well cancelled by frequency duplex method, but the elimination of far-end crosstalk (FEXT) is not so easy. Therefore FEXT is the dominant source of disturbance in current digital subscriber lines (xDSL). One of the most promising solutions for far-end crosstalk cancellation is Vectored Discrete Multi-tone modulation (VDMT). For the testing of VDMT modulation efficiency it will be necessary to implement advanced methods for modeling of far-end crosstalk to obtain required predictions of the crosstalk behavior in a cable. The actual simple FEXT model is not very accurate and does not provide realistic results. That is why the new method for modeling of far-end crosstalk was developed and is presented in this paper. This advanced model is based on the capacitive and inductive unbalances between pairs in a cable and it also respects the cable’s internal structure. The results of the model are subsequently used for the simulation of VDMT modulation and its impact on the FEXT cancellation. These simulations are based on the estimations of transmission speed of VDSL2 lines with VDMT modulation.
Keywords: Digital subscriber line; crosstalk; FEXT; VDMT modulation; VDSL2